Analisis Isi Pertanyaan Debat Calon Presiden 2024 di Youtube KOMPAS TV - Dwi Firmansyah; Oktaviana Purnamasari; Ratu Laura MBP (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2024)
The presidential debate is a crucial moment in political communication, allowing candidates to present their visions and missions to the public. This study aims to analyze the questions posed by Anies Baswedan, Prabowo Subianto, and Ganjar Pranowo during the 2024 presidential debate broadcast on YouTube KOMPAS TV, focusing on the main themes, communication styles, and rhetorical strategies employed. The method used is qualitative content analysis, where debate excerpts are analyzed based on the themes raised and the communication strategies applied by each candidate. The findings show that each candidate used a different approach in asking questions: Anies Baswedan focused on ethical issues, Prabowo Subianto addressed public policy related to unemployment, and Ganjar Pranowo raised social issues and development policies related to the relocation of the capital city. The communication styles used by each candidate varied from critical, collaborative, to urgent, reflecting their political character. This study concludes that these questions play a significant role in shaping the candidates' image and influencing public perception, especially in the context of increasingly digital political communication.